Characterization of turbulent transport of particles and optimization of plasma heating and operation current control in the coils of the SCR-1 Stellarator - Solano-Piedra, Ricardo (2026)
The SCR-1 stellarator, operational since June 2016, has emerged as a pioneer in Latin America in the field of modular stellarator devices, developed by the Costa Rica Institute of Technology. This device has been the subject of continuous characterization and optimization efforts, with a focus on significant improvements in turbulence, coil feeding and wave propagation within the SCR-1 stellarator. This work presents a first study of turbulence, examining behavior at the plasma edge and its interaction with external electric fields, as well as the importance of electrode polarization. In addition, the design of the DC-DC Buck converter for the SCR-1 current coil control system is addressed, along with the proposal of a Vlasov antenna to optimize energy deposition in the plasma. Results indicate the significant influence of electrodes on plasma behavior. A power converter was designed to ensure an efficient and safe electrical supply and simulated by PLECS. The buck converter was deemed crucial for precise and stable current regulation in the coils. Electronic components were sized to handle the required current and voltage specifications. Finally, a modified Vlasov antenna was designed, which demonstrated in COMSOL multiphysics simulations that the new configuration improved the distribution of electromagnetic waves in the SCR-1 vacuum vessel.